Activity of Gallium Meso- and Protoporphyrin IX against Biofilms of Multidrug-Resistant Acinetobacter baumannii Isolates - David Chang; Rebecca A. Garcia; Kevin S. Akers; Katrin Mende; Clinton K. Murray; Joseph C. Wenke; Carlos J. Sanchez (MDPI AG, 2016)
Acinetobacter baumannii is a challenging pathogen due to antimicrobial resistance and biofilm development. The role of iron in bacterial physiology has prompted the evaluation of iron-modulation as an antimicrobial strategy. The non-reducible iron analog gallium(III) nitrate, Ga(NO3)3, has been shown to inhibit A. baumannii planktonic growth; however, utilization of heme-iron by clinical isolates has been associated with development of tolerance. These observations prompted the evaluation of iron-heme sources on planktonic and biofilm growth, as well as antimicrobial activities of gallium meso- and protoporphyrin IX (Ga-MPIX and Ga-PPIX), metal heme derivatives against planktonic and biofilm bacteria of multidrug-resistant (MDR) clinical isolates of A. baumannii in vitro. Ga(NO3)3 was moderately effective at reducing planktonic bacteria (64 to 128 µM) with little activity against biofilms (≥512 µM). In contrast, Ga-MPIX and Ga-PPIX were highly active against planktonic bacteria (0.25 to 8 µM). Cytotoxic effects in human fibroblasts were observed following exposure to concentrations exceeding 128 µM of Ga-MPIX and Ga-PPIX. We observed that the gallium metal heme conjugates were more active against planktonic and biofilm bacteria, possibly due to utilization of heme-iron as demonstrated by the enhanced effects on bacterial growth and biofilm formation.